2022
DOI: 10.3390/plants11212867
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmocidal and Cytotoxic Activities Guided Isolation and Characterization of an Undescribed Bioflavonoid-di-C-glucoside from Cycas rumphii Miq. Cultivated in Egypt

Abstract: Toxoplasmosis and cancer are serious worldwide diseases, and the available drugs cause serious side effects. Investigation for new alternative therapies from natural sources is now an increasing concern. Herein, we carried out, for the first time, an in vitro screening of Cycas rumphii Miq. leaves for toxoplasmocidal effect, using Viruluent RH Toxoplasma gondii, and cytotoxic activity against HEPG-2, HCT-116 and HELA cancer cell lines using MTT assay. Among the tested extracts, the ethyl acetate fraction was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…The IR spectrum of compound ( 4 ) was found identical to an authentic sample of amentoflavone ( Figure S15B ). The spectral data of compound ( 4 ) was identical to those reported in the literature for amentoflavone [ 2 , 24 , 32 ].…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The IR spectrum of compound ( 4 ) was found identical to an authentic sample of amentoflavone ( Figure S15B ). The spectral data of compound ( 4 ) was identical to those reported in the literature for amentoflavone [ 2 , 24 , 32 ].…”
Section: Resultssupporting
confidence: 75%
“…The IR spectrum of compound ( 2 ) was found identical to an authentic sample of bilobetin ( Figure S8B ). By comparing our data to those reported in the literature [ 2 , 24 , 27 , 28 ], compound ( 2 ) was identified as amentoflavone 4′- O -methyl ether (bilobetin).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Additionally, in our previous study of the cytotoxic capability of C. rumphii in different extracts, we found that strong cytotoxic activity is detected in the whole methanol extract of C. rumphii against HePG-2, HeLA, and HCT-116, with IC50 values of 10.09, 11.79, and 12.58 µg/mL, respectively compared to doxorubicin as a standard drug. Interestingly, doxorubicin, the positive control, had an IC50 of 7.79 µg/mL while the entire MeOH extract of C. rumphii had an IC50 of 53.72 µg/mL against the normal cell line (WISH) 10 . As a result, it is believed that C. rumphii MeOH extracts are less harmful to healthy cells and more effective against cancer cells.…”
Section: Cytotoxic Activitymentioning
confidence: 99%